Promising therapies for the treatment of frontotemporal dementia clinical phenotypes: from symptomatic to disease-modifying drugs. (13th June 2019) - Logroscino, Giancarlo; Imbimbo, Bruno P.; Lozupone, Madia; Sardone, Rodolfo; Capozzo, Rosa; Battista, Petronilla; Zecca, Chiara; Dibello, Vittorio; Giannelli, Gianluigi; Bellomo, Antonello; Greco, Antonio; Daniele, Antonio; et al.
ABSTRACT: Introduction: Frontotemporal dementia (FTD) is a heterogeneous clinical entity that includes several disorders characterized by different cellular mechanisms. Distinctive clinical features in FTD include behavioral, affective, and cognitive symptoms. Unfortunately, little progress has been made over the past 20 years in terms of the development of effective disease-modifying drugs with the currently available symptomatic treatments having limited clinical utility. Areas covered: This article reviews the principal pharmacological intervention studies for FTD. These are predominantly randomized clinical trials and include symptomatic treatments and potential disease-modifying drugs. Expert opinion: There is insufficient evidence on effective treatments for FTD and studies with better methodological backgrounds are needed. Most studies reporting therapeutic benefits were conducted with selective serotonin reuptake inhibitors, while anti-dementia drugs have been ineffective in FTD. Since the underlying pathology of FTD mostly consists of abnormal tau protein or TDP-43 aggregates, treatments are being developed to interfere with their aggregation process or with the clearance of these proteins. Furthermore, disease-modifying treatments remain years away as demonstrated by the recent negative Phase III findings of a tau aggregation inhibitor (LMTM) for treating the behavioral variant of FTD. The results from current ongoing Phase I/II trials will hopefully give light to future treatment options.